EDUKASI PEMANFAATAN TANAMAN OBAT: DAUN LANDEP SEBAGAI ALTERNATIF HERBAL PENURUN KOLESTEROL DI KELURAHAN GEDANGAN KECAMATAN GROGOL KABUPATEN SUKOHARJO - M. Saiful amin; Esa kiara frista O; Devi Indriyanti; Carolina Nieva S; Hildha Dwi Rahmawati; Ovikariani (LPPM Universitas Awal Bros, 2026)
Educational activities on the Utilization of Medicinal Plants: Landep Leaves (Barleria prionitis L.) as an Alternative Herbal Cholesterol Lowering in Gedangan Village, Grogol District, Sukoharjo Regency were motivated by the high prevalence of hypercholesterolemia as a risk factor for cardiovascular disease, as well as the low utilization of family medicinal plants (TOGA), especially landep leaves which have anti-cholesterol potential. The implementation method included health education on hypercholesterolemia and the benefits of landep leaves, as well as practical training on processing landep leaves into herbal tea. The target of the activity was the Gedangan Village community, especially PKK mothers and health cadres. Evaluation was carried out using pre-tests and post-tests to measure increased knowledge, as well as a satisfaction index questionnaire from LPPM. The results of the activity showed an increase in participant knowledge by 13% (the average pre-test score was 7.70 increasing to 8.70), with the results of the paired t-test showing a p value = 0.000 (p < 0.05), which means a statistically significant increase. Furthermore, the activity received a very satisfactory rating with an average satisfaction score of 4.997. Participants also gained practical skills in processing landep leaves into herbal tea, which has the potential to be developed as a simple health product or a local business opportunity. Overall, this activity proved beneficial in increasing public knowledge, skills, and awareness regarding the use of herbal plants. Sustainability of the program is recommended through mentoring, monitoring, and the development of cross-sector collaboration to support broader and more sustainable herbal use